Azobispyrazole Family as Photoswitches Combining (Near‐) Quantitative Bidirectional Isomerization and Widely Tunable Thermal Half‐Lives from Hours to Years. (17th June 2021) - He, Yixin; Shangguan, Zhichun; Zhang, Zhao‐Yang; Xie, Mingchen; Yu, Chunyang; Li, Tao
Abstract: Azobenzenes are classical molecular photoswitches that have been widely used. In recent endeavors of molecular design, replacing one or both phenyl rings with heteroaromatic rings has emerged as a strategy to expand molecular diversity and access improved photoswitching properties. Many mono‐heteroaryl azo molecules with unique structures and/or properties have been developed, but the potential of bis‐heteroaryl architectures is far from fully exploited. We report a family of azobispyrazoles, which combine (near‐)quantitative bidirectional photoconversion and widely tunable Z ‐isomer thermal half‐lives from hours to years. The two five‐membered rings remarkably weaken the intramolecular steric hindrance, providing new possibilities for engineering the geometric and electronic structure of azo photoswitches. Azobispyrazoles generally exhibit twisted Z ‐isomers that facilitate complete Z → E photoisomerization, and their thermal stability can be broadly adjusted regardless of the twisted shape, overcoming the conflict between photoconversion (favored by the twisted shape) and Z ‐isomer stability (favored by the orthogonal shape) encountered by mono‐heteroaryl azo switches. Abstract : Azobispyrazoles are a family of bis‐heteroaryl azo photoswitches that combine excellent E ⇆ Z photoisomerization yields and widely tunable Z ‐isomer thermal half‐lives from hours to years, showing the great potential of Het‐N=N‐Het architecture in developing high‐performance molecular photoswitches.